The extent of changes in the membranous urethra angle is associated with the outcome of retrourethral transobturator sling procedure - Soljanik, Irina (International urology and nephrology, 2015)
PurposeTo evaluate the outcome of the retrourethral transobturator sling (RTS) by functional magnetic resonance imaging (MRI) and to identify parameters associated with sling failure.MethodsOf thirty recruited men with postprostatectomy stress urinary incontinence (SUI), 26 consecutively underwent functional MRI before sling procedure and 12 months thereafter in a prospective clinical cohort observational study. Periurethral/urethral fibrosis and sling visualization were evaluated on static sequences. The angle of the membranous urethra, position of the bladder neck and external urethral sphincter were assessed during Valsalva’s maneuver and voiding. Sling success was defined as no or one dry “security” pad.ResultsThe success and failure rates were 58 % (15/26 patients) and 42 % (11/26 patients), respectively. The sling leads to reduction in the membranous urethra angle during Valsalva’s maneuver (39.55° vs. 36.82°, p = 0.025) and voiding (38.25° vs. 34.83°, p = 0.001) and elevation of the external urethral sphincter (2.9 vs. 4.8 mm, p = 0.017). Preoperative wider angle of the membranous urethra was significantly correlated with severe preoperative incontinence. Sling failure (p = 0.001) and severe preoperative incontinence (p = 0.001) were significantly related to only small changes of the membranous urethra angle. The interrater and intrarater reliability for membranous urethra angle was excellent (intraclass correlation coefficient ≥0.75).ConclusionsThe RTS leads to reduction in the membranous urethra angle. The extent of the changes in the membranous urethra angle is associated with RTS outcome. Functional MRI is a reliable noninvasive visualization tool of interactions between the sling and pelvic floor for further research on the complex nature of postprostatectomy SUI.